Kajian Ekspansi Akasia di Taman Wisata Alam Bukit Tangkiling - Siti Maimunah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2015)
The aim of the research is to know the values of acacia expansion in Taman Wisata Alam Bukit Tangkiling at 500 ha at Bukit Batu district of Palangka Raya The conditions of Taman Wisata Alam Bukit Tangkiling have done reforestasi but this area hsve a specific vegetation there are acacia domination. Acacia"s root have a allelopaty matter, itscia can be erwenom to other plant then acacia can be expansi to all area. The method of this research is Vegetation analysis to know stand potention with 3 strip sampling 100 x 20 m with gap between strip are 50 meter. Intensitas sampling 0,12% for area 500 ha. The result of this research is the value of acacia expansion in TWA Bukit Tangkiling is 63,71%. This monitoringis canbe use to be a database, and scientiJic studies to definite some treotment to solve this expansion and save the endemic species in TIIA Bukit'fangkiling.